Efficacy and Safety of 10‐Day Versus 14‐Day Bismuth‐Containing Quadruple Therapy for Helicobacter pylori Eradication: A Systematic Review and Meta‐Analysis - Najam Gohar; Zoya Ejaz; Faizan Ahmed; Abdul Rafay Ahmed; Muhammad Abdullah Humayun; Momna Nisar; Muhammad Ali Mushtaq; Aanusha Ghouri; Fatima Zafar; Hira Khalid; Sania Afzal; Hammad Khan; et al. (JGH Open)
ABSTRACT Background Nearly half of the world population is infected by Helicobacter pylori (H. pylori). Bismuth‐containing quadruple therapy (BQT) has shown favorable outcomes. This study compares 10‐day and 14‐day BQT regimens to evaluate their efficacy, safety, and compliance rates. Methods We searched electronic databases from their inception until May 2024 to retrieve all randomized controlled trials (RCTs) that compared 10‐day and 14‐day BQT regimens for H. pylori eradication. Meta‐analysis was performed using Review Manager 5.4. Dichotomous outcomes were compared using the risk ratio (RR). Results Seven RCTs and a total of 2424 patients were included in the meta‐analysis. There was no significant difference in the intention‐to‐treat eradication rate (RR 0.97; 95% CI 0.94, 1.01) and the per‐protocol eradication rate (RR 0.96; 95% CI 0.93, 1.00) between the 10‐day BQT and 14‐day BQT groups. Commonly reported adverse events in both groups were epigastric pain and discomfort, nausea, and vomiting. There was no significant difference in the risk of adverse events between the two groups (RR 0.85; 95% CI 0.70, 1.03). There was no significant difference in the compliance rate between the two groups (RR 1.02; 95% CI 1.00, 1.04). Conclusion The eradication rates, risk of adverse events, and compliance rates were comparable between the two groups. Future research comparing similar drug doses with larger sample sizes and longer patient follow‐ups can improve the quality of results.